The Strategic Effect of Hedonic and Utilitarian Value in Building Brand Trust and Brand Satisfaction - Francis Osei; Joyce Dankwah Owusu; Collins Kankam-Kwarteng (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
Customer value, divided into hedonic (emotional) and utilitarian (functional) dimensions, is crucial for competitive advantage, prompting the need for research in diverse contexts. Existing literature highlights the strategic importance of balancing these values to enhance brand trust and satisfaction, yet the cosmetics industry in Ghana remains underexplored. This study gathered data from 200 cosmetic product users in Ghana and used structural equation modelling to analyze the relationships between hedonic and utilitarian values, brand trust, and brand satisfaction. The findings indicate that hedonic values do not significantly affect brand trust or satisfaction, while utilitarian values are key drivers of both. Brand trust positively influences brand satisfaction but does not mediate the relationship between hedonic values and satisfaction. However, brand trust mediates the connection between utilitarian values and satisfaction. These insights are valuable for scientists studying consumer behaviour and for marketers aiming to meet customer expectations more effectively. This study, among the first of its kind in Ghana, underscores the strategic importance of utilitarian values in building brand trust and satisfaction in the cosmetic industry. Limitations include a single geographic focus and industry, suggesting future research should explore other contexts and include variables like brand loyalty and socioeconomic status to enhance understanding.